Pengembangan Media Lapbook untuk Pembelajaran IPA Materi Hewan Invertebrata di Kelas IV MI Al Barokah - Anugraini, Putri Salsabilah; Prayogo, Muhammad Suwignyo; Imelliya, Febbi; Afkarina, Fika (STKIP HARAPAN BIMA, 2025)
Interactive learning media play an essential role in facilitating effective communication between teachers and students. This study aims to improve students’ science learning outcomes on the topic of invertebrate animals through the use of lapbook learning media in Grade IV at MI Al Barokah An-Nur. The method employed was Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, acting, observing, and reflecting stages conducted over two cycles. The research subjects were 20 fourth-grade students. Data were collected through learning outcome tests, observations of student activities, and documentation in the form of photos and field notes. Data were analyzed quantitatively by calculating the average scores and mastery learning percentages, and qualitatively through data reduction, data display, and conclusion drawing. The results showed a significant improvement across cycles. The average score increased from 63 in the pre-cycle to 75 in Cycle I and 83 in Cycle II. The mastery learning percentage also increased from 70% in Cycle I to 85% in Cycle II. Moreover, all student groups demonstrated active collaboration and engagement during the lapbook creation and presentation activities. Based on these findings, it can be concluded that the use of lapbook media is effective in enhancing science learning outcomes, student participation, and learning experiences.